Gonal F and Cinal F drugs on infertility treatment in ICSI cycle in Milad Infertility Center - Faizeh Mashhadi; Malihe Mahmoudinia; Tahere Sadeghi; Nafiseh Jahanpak; Nayereh Khadem (Mashhad University of Medical Sciences, 2022)
Introduction: Gonadotropins are the main drugs for ovarian stimulation in assisted reproductive cycles. There are many different types of urine, purified or recombinant gonadotropins. This study was performed aimed to compare the clinical outcomes of two types of recombinant Cinal F gonadotropin Iranian company and Gonal F of foreign company.                                 Methods: This retrospective study was conducted in 2015-2019 on 521 infertile women (263 Cinal F and 258 Gonal F) who were referred to Milad Center affiliated to Mashhad University of Medical Sciences and were candidate for IVF. Clinical Outcomes including number of follicles, number of obtained oocytes, number of metaphase1 and 2 oocytes, number of high-quality embryos, rate of ovarian hyperstimulation syndrome, and positive pregnancy test were compared in Cinal F and Gonal F groups. Data were analyzed by SPSS statistical software (version 23) and Independent t-test and chi-square test. P<0.05 was considered statistically significant. Results: The incidence of ovarian hyperstimulation syndrome and positive pregnancy test was not significantly different in the two groups (P> 0.05). In the Gonal F group, the percentage of good embryo quality was better than Cinal F group (p = 0.017). The number of total follicles and oocytes, metaphase 1 and 2 oocytes and the number of necrotic and low-quality oocytes, and the number of embryos and frozen embryos were not significantly different (P> 0.05). Conclusion: In this study, there was no evidence in favor of the difference between cinal and foreign drug in the success rate of assisted reproductive cycles. Regarding to the scarcity and high cost of Gonal F, Cinal can be used with confidence in the IVF cycle.